1986
DOI: 10.1111/j.1399-6576.1986.tb02385.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous regional anaesthesia for foot surgery

Abstract: Intravenous regional anaesthesia, confined to the distal lower limb and using bupivacaine 0.25%, was studied in 12 patients undergoing orthopaedic procedures to the feet. The technique was well accepted by both surgeons and patients and was free from serious toxicity. Bupivacaine was demonstrated in the systemic venous circulation in every case prior to surgery, whilst the tourniquet remained deflated. The plasma bupivacaine levels were less than that associated with toxicity, except in one case exhibiting sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The relatively high plasma concentrations of lidocaine measured in the majority of cats prior to tourniquet removal in the present study despite the application of two tourniquets was unexpected, although recovery of small amounts of lidocaine would not have been surprising. Despite adequate and sustained tourniquet pressures, leakage of local anesthetic into the circulation has been reported and investigated in human patients (Rosenberg et al 1983;Davies & Walford 1986;Ho¡mann et al 1995;Coleman et al 1999). Leaks were quanti¢ed by measuring the radioactivity remaining in the limb after injection of a radiolabeled substance in humanvolunteers (Coleman 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively high plasma concentrations of lidocaine measured in the majority of cats prior to tourniquet removal in the present study despite the application of two tourniquets was unexpected, although recovery of small amounts of lidocaine would not have been surprising. Despite adequate and sustained tourniquet pressures, leakage of local anesthetic into the circulation has been reported and investigated in human patients (Rosenberg et al 1983;Davies & Walford 1986;Ho¡mann et al 1995;Coleman et al 1999). Leaks were quanti¢ed by measuring the radioactivity remaining in the limb after injection of a radiolabeled substance in humanvolunteers (Coleman 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Despite adequate and sustained tourniquet pressures, leakage of local anesthetic into the circulation has been reported and investigated in human patients (Rosenberg et al. 1983; Davies & Walford 1986; Hoffmann et al. 1995; Coleman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous regional anesthesia (IVRA) is often used in short and minor extremity surgeries given its ease and simplicity. However, it is limited by local anesthetic systemic toxicity reactions, the placement of tourniquets, and poor anesthetic outcomes, which result in a poor patient experience and place the anesthesiologist in a relatively passive position [ 48 , 49 , 50 ]. Weldon et al [ 25 ] investigated the effects of local anesthesia with bupivacaine nanoencapsulation in a rat intracaudal vein local anesthesia model.…”
Section: Application Of Nanotechnology In the Anesthesia Fieldmentioning
confidence: 99%
“…Some authors have reported that the use of an under-knee tourniquet does not increase the risk of local anaesthetic leakage from the interosseous space; it allows a lower dose to obtain a comparable level of anaesthesia and is as safe as an over-knee tourniquet. [4] We believe that this innate plasticity of IVRA may be optimised by alternative adaptations for the lower extremity. An additional tourniquet at the below-knee level may limit the distribution of local anaesthetic.…”
mentioning
confidence: 99%